Early onset cardiovascular disease related to methamphetamine use is most striking in individuals under 30: A retrospective chart review - Vinita Batra; Kevin S. Murnane; Brianne Knox; Amber N. Edinoff; Yahya Ghaffar; Laura Nussdorf; Murray Petersen; Sarah E. Kaufman; Sania Jiwani; Christopher A. Casey; Stephanie Terhoeve; Mohammad Alfrad Nobel Bhuiyan; et al. (Addictive Behaviors Reports, 2022)
Introduction: The illicit use of methamphetamine (MA), a dangerous psychostimulant has become a global epidemic. Studies have demonstrated a link between illicit substance use and cardiovascular consequences. The objective of this study was to assess whether MA use is associated with an early onset of cardiovascular diseases (CVD). Methods: Retrospective analysis was conducted using data collected from 1376 individuals at Louisiana State University Health Sciences Center - Shreveport between 2011 and 2020. Cardiovascular patients with and without a history of MA use were divided into the MA and Control groups. The age of CVD onset was assessed. Descriptive statistics for patient characteristics, Two Samples T-Test for continuous and Pearson's χ^2- tests for categorical variables were calculated. Hazard ratios (HR) and time ratios (TR) were calculated. Results: The age of CVD onset in patients with prior MA use occurred on average 8 year earlier than the age of CVD onset (mean age ± SD = 44 ± 12.04) in controls (mean age ± SD = 52 ± 10.70) (unpaired t-test, p < 0.0001). The findings were noted in both the races (Time Ratio = 0.93, 95% CI = 0.89 to 0.97, p-value < 0.001), with a striking difference in the latency to CVD onset between Black and White subjects. A 12-fold increase in subjects who showed a premature onset of CVD (<30 years of age) in the MA group was observed. Our data analysis revealed that hypertension was the most frequently observed CVD. Conclusions: MA use likely accelerates early onset of CVD and contributes to CVD complications in young adults.